Flouting Maxim Dalam Komedi “Lapor Pak” di Trans7 - Prapti Wigati Purwaningrum; Danang Dwi Harmoko (LPPM Universitas Bina Sarana Informatika, 2022)
The purpose of this research is to explore several flouting of maxims, including maxims of quantity, maxim of quality, maxim of relevance spoken by the performers of the comedy